2014
DOI: 10.1523/jneurosci.5069-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mutant α-Synuclein Enhances Firing Frequencies in Dopamine Substantia Nigra Neurons by Oxidative Impairment of A-Type Potassium Channels

Abstract: Parkinson disease (PD) is an ␣-synucleinopathy resulting in the preferential loss of highly vulnerable dopamine (DA) substantia nigra (SN) neurons. Mutations (e.g., A53T) in the ␣-synuclein gene (SNCA) are sufficient to cause PD, but the mechanism of their selective action on vulnerable DA SN neurons is unknown. In a mouse model overexpressing mutant ␣-synuclein (A53T-SNCA), we identified a SN-selective increase of in vivo firing frequencies in DA midbrain neurons, which was not observed in DA neurons in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 48 publications
10
112
1
Order By: Relevance
“…This could help to explain the differential vulnerability of VTA and SNc DA neurons to α-syn overexpression 20,22 . Along these same lines, a recent study has demonstrated that in mouse SNc DA neurons, but not in neighbouring VTA DA neurons, the oxidant stress that is induced by α-syn overexpression triggered an increase in pacemaking rate 135 ; this effect presumably reflects the ability of pre-existing or baseline oxidant stress in SNc DA neurons to sum with that created by α-syn overexpression.…”
Section: Cell-autonomous Determinants Of Cpd Pathologymentioning
confidence: 95%
“…This could help to explain the differential vulnerability of VTA and SNc DA neurons to α-syn overexpression 20,22 . Along these same lines, a recent study has demonstrated that in mouse SNc DA neurons, but not in neighbouring VTA DA neurons, the oxidant stress that is induced by α-syn overexpression triggered an increase in pacemaking rate 135 ; this effect presumably reflects the ability of pre-existing or baseline oxidant stress in SNc DA neurons to sum with that created by α-syn overexpression.…”
Section: Cell-autonomous Determinants Of Cpd Pathologymentioning
confidence: 95%
“…Notably, surviving DA neurons in PD exhibit increased NMDA receptor subunit NR1 and K-ATP subunit expression, and display up to 2-fold enhanced bursting rates. These studies suggest that enhanced in vivo burst firing might contribute to the selective vulnerability of DA SNc neurons, possibly reflecting an acquired vulnerability process (Liss et al, 2005;Schiemann et al, 2012;Subramaniam et al, 2014). Taken together, several studies suggest that vulnerable SNc DA neurons exhibit reduced excitation due to reduced mitochondrial function and enhanced cytosolic calcium levels in PD, leading to silencing and subsequent degeneration of vulnerable neurons (Figure 1).…”
Section: Introductionmentioning
confidence: 89%
“…However, to date, there has been no attempt to determine whether inhibition of Cav1 channels blunts the toxicity of αSYN fibrils in vivo. What has recently been shown is that over-expression of αSYN increases oxidant stress in SNc DA neurons (see [90])and, in so doing, down-regulates the function of K + (Kv4) channels that slow the spiking rate [115]. Thus, the convergence of LP and mitochondrial stress could force SNc DA neurons into a ‘death spiral’, where growing oxidant stress elicits an increase in firing rate that further augments bioenergetic demand…”
Section: Does the Unusual Use Of Ca2+ By At-risk Neurons Cause Pd?mentioning
confidence: 99%